Powtoon Learning Media Containing Local Wisdom Improves Elementary School Social Sciences Learning Outcomes - Devita Dwi Permatasari; Novi Setyasto (Universitas Pendidikan Ganesha, 2024)
The lack of social studies learning media has an impact on low student learning outcomes. This research aims to develop powtoon learning media containing local wisdom to improve elementary school social studies learning outcomes. This type of research is Research and Development (R&D) using the Borg and Gall development model. This research involved media experts and material experts. The test subjects for this research were 26 elementary school IV student participants. Data collection were carried out using interviews, observation, documentation, questionnaires and tests. This research uses questionnaire instruments and test questions in data collection. The data collected was analyzed using qualitative, quantitative, and t-test descriptive analysis. The results of the research show that Powtoon learning media containing local wisdom was declared